University of the Autonomous Regions of the Nicaraguan Caribbean Coast and its Community Accompaniment - Williams Muller, Elebe (Revista Universitaria del Caribe, 2019)
The University of the Autonomous Regions of the Nicaraguan Caribbean Coast was created from and for the native peoples of the Caribbean Coast of Nicaragua. This has meant that, its actions are based on accompanying development processes; but, also in revitalizing the knowledge and practices of the people who live in the region. The different actions carried out are aimed at: the offering of relevant careers for the region, studying the conditions in which native women in the region are and making proposals that lead to a more equitable relationship between men and women, monitoring of natural resources, study and promotion of autonomy, revitalization of traditional knowledge that improves people's health, linguistic research and cultural revitalization and support for the exploitation of resources in a sustainable way. The components approached from the university come to respond to the most elementary needs of a people and the reaffirmation of their identity, their resources and their culture. In addition, it implies carrying out processes of accompaniment to the regional authorities for a more conscious decision making that is based on the well-being of the people who live in the Caribbean Coast of Nicaragua.